Edukasi Pemilahan Sampah Kepada Masyarakat Tanjung Uncang RT 01 RW 15 - Christofher, Leonardo; Robin, Robin; Erline, Meillverrani; Cung, Jimmy; Wily, Wily; Febrianna, Maudy; Tan, Helen; Aprilla, Enje; Surya, Mellitania; Agustin, Greece; Gresia, Silvy; Diana, Diana; Lim, Angellyn; Susanto, Agus (National Conference for Community Service Project (NaCosPro), 2019)
Garbage is a part of human life that?s an object/remaining substance that?s no longer useful. Waste should receive attention and serious treatment. However, due to the lack of understanding from the community and the government, insufficient funding and revenue of the majority of community, hence this waste problem has been neglected. Today, most people have already understood the problems that may be caused by the garbage, for instance floods, diseases and smell that can disrupt the daily lives of our community. However, this isn?t accompanied by the action of the people themselves. The purpose of this study is to spread public awareness on how to properly treat waste and how to distinguish types of organic and inorganic waste. This study is also to find out the benefits that can be obtained from waste, build a healthy environment that?s free from pollution, and find a solution to environmental sanitation, specifically rural waste management. This research was conducted at Tanjung Uncang RT 01 RW 15. Research data collection was done based on our observations. The result obtained from the research shows a lack of action from Tanjung Uncang community against waste. From the research conducted by the author, it can be concluded that the people of Tanjung Ucang have good knowledge about waste but bad behavior towards garbage management, mostly due to the lack of attention from the local government who are supposed to be able to handle waste problems.